Granulomatous enteritis associated with porcine proliferative enteropathy - Machuca, Mariana A.; Cappuccio, Javier A.; Quiroga, Maria A.; Insarralde, Lucas; Cancer, Jose L.; Arrospide, Silvio; Perfumo, Carlos J. (Brazilian Journal of Veterinary Pathology, 2012)
An outbreak of proliferative hemorrhagic enteropathy in a commercial pig farm, characterized by granulomatous enteritis, was studied by slaughter checks and by histopathological, histochemical and immunohistochemical studies. Six of the postmortem examined pigs (117-122-day-old) with diagnosis of porcine proliferative enteropathy (PPE) showed granulomatous enteritis and 4.3% of the 465 slaughtered pigs showed gross lesions of PPE. A total of 33 of the 66 ileum samples had histopathological changes, whereas 17 of them had granulomatous enteritis and PPE lesions. Lawsonia intracellularis was immunolabeled in 52 of the ileum samples in epithelial cells and within granulomatous inflammation in Peyer´s patches and in 28 samples of mesenteric lymph nodes. Porcine circovirus type 2 was only detected by immunohistochemistry in 4 ileum samples and in 5 mesenteric lymph nodes. Since there was a strong statistically significant association between granulomatous enteritis and L. intracellularis infection, granulomatous enteritis could be considered as a part of the PPE complex.